Eloise has a lesson - McNamara, Margaret; Mitter, Kathy; Knight, Hilary (New York : Aladdin Paperbacks, 2005)
Eloise would rather tease her tutor, Philip, than let him teach her math.
"Level 1, Starting to Read"--P. [4] of cover.
"Based on the art of Hilary Knight"--P. [1] of cover.
Keywords: Teachers; Teasing; Arithmetic